Aspects of Music in Canada - Walter, Arnold (Book collections on Project MUSE., 1969)
Composition, performance (live and on the air), and education are surveyed and carefully documented. Essays on history, on folk and aboriginal music, and on musical organizations are also included. All who are intersted in the role that music has played and is playing in Canadian life will welcome this book of essays.